Interregional Transmission of the Internal Protein Genes of H2 Influenza Virus in Migratory Ducks from North America to Eurasia - Liu, Jin-Hua; Okazaki, Katsunori; Bai, Gui-Rong; Shi, Wei-Min; Mweene, Aaron; Kida, Hiroshi (Virus genes, 2004)
H2 influenza virus caused a pandemic in 1957 and has the possibility to cause outbreaks in the future. To assess the evolutionary characteristics of H2 influenza viruses isolated from migratory ducks that congregate in Hokkaido, Japan, on their flyway of migration from Siberia in 2001, we investigated the phylogenetic relationships among these viruses and avian and human viruses described previously. Phylogenetic analysis showed that the PB2 gene of Dk/Hokkaido/107/01 (H2N3) and the PA gene of Dk/Hokkaido/95/01 (H2N2) belonged to the American lineage of avian virus and that the other genes of the isolates belonged to the Eurasian lineage. These results indicate that the internal protein genes might be transmitted from American to Eurasian avian host. Thus, it is further confirmed that interregional transmission of influenza viruses occurred between the North American and Eurasian birds. The fact that reassortants could be generated in the migratory ducks between North American and Eurasian avian virus lineage further stresses the importance of global surveillance among the migratory ducks.